Affective Meaning in "The Kissing Booth" Movie Script Movie - Lisnawati Safiuddin; Ansor Putra (ELITE: Journal of English Language and Literature, 2021)
This study aims to analyze â€œThe Kissing Booth movie scriptâ€ in terms of semantic study. The research question of this study is â€œHow is Affective meaning used in The Kissing Booth Movie Script by Beth Reekles?â€. The objective of this study is to describe affective meaning is used in â€˜The Kissing Boothâ€™ Movie Script by Beth Reekles. The source of data is taken from the movie script by Beth Reekles. This study uses the descriptive qualitative method. The data are collected by searching and downloading, watching the movie, reading the script, classifying, and coding the data. Based on the analysis the writer finds affective meaning such as positive and negative affective meaning. Positive affective meaning consists of three data was (happy data 1 and 2, flattered data 3) and negative affective meaning consists of 12 data that are (angry data 4, 6, 9, 11, 12, shocked data 8 and 13, disappointed data 7 and 14, unhappy data 10, sad data15). The most dominant implication in the movie script objects is the emotion of negative affective meaning. The use of affective meaning depends on the context of the situation that occurs when the utterances stated.